2013
DOI: 10.1016/j.bbamcr.2013.02.031
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induces podocyte apoptosis by stimulating TRPC6 via elevation of reactive oxygen species

Abstract: Podocyte number is significantly reduced in diabetic patients and animal models, but the mechanism remains unclear. In the present study, we found that high glucose induced apoptosis in control podocytes which express transient receptor potential canonical 6 (TRPC6) channels, but not in TRPC6 knockdown podocytes in which TRPC6 was knocked down by TRPC6 silencing short hairpin RNA (shRNA). This effect was reproduced by treatment of podocytes with the reactive oxygen species (ROS), hydrogen peroxide (H2O2). Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 31 publications
8
75
0
Order By: Relevance
“…Our study is the first Podocytes are inter-connected by slit diaphragms (SDs) that covered the exterior basement membrane surface of the glomerular capillary and maintain the structural integrity of glomerular capillary loops. Recently, several studies have demonstrated that podocyte apoptosis plays a key role in the pathogenesis of DN [19][20][21][22] . Thus, preventing or inhibiting podocyte apoptosis may provide an obvious therapeutic modality for DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first Podocytes are inter-connected by slit diaphragms (SDs) that covered the exterior basement membrane surface of the glomerular capillary and maintain the structural integrity of glomerular capillary loops. Recently, several studies have demonstrated that podocyte apoptosis plays a key role in the pathogenesis of DN [19][20][21][22] . Thus, preventing or inhibiting podocyte apoptosis may provide an obvious therapeutic modality for DN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in podocytes has identified three biochemically distinct classes of stimuli that cause TRPC6 channels to become active: canonical lipid signals such as DAG generated during G protein signaling, for example, AT 1 receptors for Ang II (Anderson et al, 2014); mechanical stimuli, which appear to act directly on the channel complex and which proceed independent of any G protein signaling in these cells ; and oxidative effects caused by agents or treatments that increase the local concentration of reactive oxygen species (Kim et al, 2012Liu et al, 2013) and that increase steady-state surface expression of TRPC6 channels in podocytes. These stimuli can produce additive effects on total TRPC6 activation, and we have presented evidence that reactive oxygen species generated by NADPH oxidases play an important role in mobilization of TRPC6 channels in response to circulating and locally produced factors such as Ang II (Anderson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…TRPC6 channels can also be activated by mechanical stimuli in podocytes , and their expression on the podocyte cell surface is increased by oxidative stress (Kim et al, 2012a,b;Liu et al, 2013). Activation of TRPC6 channels leads to the influx of Ca 21 and other cations, which in turn causes activation of a variety of downstream effectors including calcineurin, RhoA, and Ca…”
mentioning
confidence: 99%
“…Hyperglycemia is the most outstanding characteristic of DM, while prolonged or chronic elevation of glucose can cause serious late complications, such as diabetic retinopathy, diabetic nephropathy, and diabetic neuropathy, which would bring significant decrease in life quality. A cascade of interconnected biochemical events, such as over-production of reactive oxygen species and damnification of ER homeostasis, initiated by hyperglycemia, have been demonstrated to affect cellular and organelle function, resulting in abnormality of organ function and the progression of diabetic complications [3][4][5]. Endoplasmic reticulum, a widespread existing intracellular organelle, serves as a site for the synthesis, folding, and modification of proteins as well as the store of calcium, and thus plays a crucial role in the maintenance of cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%